BEBERAPA CATATAN TERHADAP KITAB-KITAB KARYA ULAMA MINANGKABAU PADA PERMULAAN ABAD XX - Pramono Pramono; Zahir Ahmad (Jurnal Elektronik WACANA ETNIK, 2013)
The Kitabs (manuscripts and printed) of Minangkabau Scholars in the Early Twentieth Century are an important local sources in reconstructing the multicultural reconstruction of local Islamic. Era of the transmission of ideas and Islamic reformation movement in West Sumatra that began in the early twentieth century has given birth to two kinds of religious groups, namely "Kaum Tua" or "traditionalists" and "Kaum Muda" or "The Modernist" which have polemics each other. Islamic polemic had a positive effect on the proliferation of copying and writing traditions of the manuscript. Many ulama or sheikh from each group write and copy the script to argue with opinions which he said is not true. Therefore, these manuscripts are important and can be a source of authentic Islamic in seeing the dynamics of Islamic conflict and resolution in West Sumatra.